Preparation and dielectric properties of barium iron niobate by molten-salt synthesis - Tawichai,N. (Elsevier Limited, 2015)
In this work, barium iron niobate; BaFe 0.5Nb 0.5O 3 powder has been successfully synthesized by molten salt method. The power was characterized by a variety technique. Pure phase perovskite was obtained at relative low calcination temperature of <700°C. The powder exhibits a fine grain with a relatively uniform particle size and microstructure. In addition, BaFe 0.5Nb 0.5O 3 ceramics were prepared and its dielectric properties were investigated. The result suggested that the ceramic prepared from molten-salt synthesis may be has a better properties than that of the ceramics synthesized by a conventional method. © 2011 Elsevier Ltd and Techna Group S.r.l.